Design of a Wireless Charging System for e-Scooter - Skorvaga, Jakub; Frivaldsky, Michal; Pavelek, Miroslav (Elektronika ir Elektrotechnika, 2021)
This article deals with the design and practical evaluation of a wireless charging system for e-scooters. As wireless charging undertakes popularity, initially, the state of the art within application area is realized. Consequently, due to variability of the configuration of the whole system, several alternatives are discussed considering the utilization of the power converter stages. High attention is given to the construction of the coupling elements and calculation of the main circuit components of the considered power converters. The experimental part of the paper is supported by the measurements of key properties, i.e., the operational characteristics of the whole converter system together with coupling coils. Here, the efficiency characteristics, together with the output power characteristics in dependency on the mutual distance between the transmitting and receiving coils, are evaluated. Received results represent an adequate design approach and practical use of the proposed Wireless Power Transfer (WPT) e-scooter charging configuration.